Development and long‐term stability of a comprehensive daily QA program for a modern pencil beam scanning (PBS) proton therapy delivery system. Issue 4 (28th March 2019) - Rana, Suresh; Bennouna, Jaafar; Samuel, E. James Jebaseelan; Gutierrez, Alonso N.
Abstract: Purpose: The main purpose of this study is to demonstrate the clinical implementation of a comprehensive pencil beam scanning (PBS) daily quality assurance (QA) program involving a number of novel QA devices including the Sphinx/Lynx/parallel‐plate (PPC05) ion chamber and HexaCheck/multiple imaging modality isocentricity (MIMI) imaging phantoms. Additionally, the study highlights the importance of testing the connectivity among oncology information system (OIS), beam delivery/imaging systems, and patient position system at a proton center with multi‐vendor equipment and software. Methods: For dosimetry, a daily QA plan with spot map of four different energies (106, 145, 172, and 221 MeV) is delivered on the delivery system through the OIS. The delivery assesses the dose output, field homogeneity, beam coincidence, beam energy, width, distal‐fall‐off (DFO), and spot characteristics — for example, position, size, and skewness. As a part of mechanical and imaging QA, a treatment plan with the MIMI phantom serving as the patient is transferred from OIS to imaging system. The HexaCheck/MIMI phantoms are used to assess daily laser accuracy, imaging isocenter accuracy, image registration accuracy, and six‐dimensional (6D) positional correction accuracy for the kV imaging system and robotic couch. Results: The daily QA results presented herein are based on 202 daily sets of measurements over a period of 10 months. Total time to perform daily QA tasks at our center is under 30 min. The relative difference (Δrel ) of daily measurements with respect to baseline was within ± 1% for field homogeneity, ±0.5 mm for range, width and DFO, ±1 mm for spots positions, ±10% for in‐air spot sigma, ±0.5 spot skewness, and ±1 mm for beam coincidence (except 1 case: Δrel  = 1.3 mm). The average Δrel in dose output was −0.2% (range: −1.1% to 1.5%). For 6D IGRT QA, the average absolute difference (Δabs ) was ≤0.6 ± 0.4 mm for translational and ≤0.5° for rotational shifts. Conclusion: The use of novel QA devices such as the Sphinx in conjunction with the Lynx, PPC05 ion chamber, HexaCheck/MIMI phantoms, and myQA software was shown to provide a comprehensive and efficient method for performing daily QA of a number of system parameters for a modern proton PBS‐dedicated treatment delivery unit.